2023
DOI: 10.3390/microorganisms11020307
|View full text |Cite
|
Sign up to set email alerts
|

Luteibacter flocculans sp. nov., Isolated from a Eutrophic Pond and Isolation and Characterization of Luteibacter Phage vB_LflM-Pluto

Abstract: Luteibacter is a genus of the Rhodanobacteraceae family. The present study describes a novel species within the genus Luteibacter (EIF3T). The strain was analyzed genomically, morphologically and physiologically. Average nucleotide identity analysis revealed that it is a new species of Luteibacter. In silico analysis indicated two putative prophages (one incomplete, one intact). EIF3T cells form an elliptical morphotype with an average length of 2.0 µm and width of 0.7 µm and multiple flagella at one end. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…The presence of xanthomonadin in our identified species indicates its importance as a prominent member of the rice microbiome, alongside NPX species. Notably, a recently published study on a novel species, L. flocculans , also reported the possibility of xanthomonadin biosynthesis in this genus, as evidenced by antiSMASH results (Friedrich et al, 2023a). In the comparative analysis of the xanthomonadin BGC ( Fig.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…The presence of xanthomonadin in our identified species indicates its importance as a prominent member of the rice microbiome, alongside NPX species. Notably, a recently published study on a novel species, L. flocculans , also reported the possibility of xanthomonadin biosynthesis in this genus, as evidenced by antiSMASH results (Friedrich et al, 2023a). In the comparative analysis of the xanthomonadin BGC ( Fig.…”
Section: Resultsmentioning
confidence: 88%
“…In addition to carbohydrates, PPL193 T was also able to utilize a range of other substrates, including L-alanine, L-glutamic acid, L-serine, tetrazolium violet, tetrazolium blue, and Llactic acid. Comparison of PPL193 T with other Luteibacter species (Akter and Huq, 2018;Friedrich et al, 2023a;Friedrich et al, 2023b;Joe et al, 2023;Johansen et al, 2005;Kampfer et al, 2009;Wang et al, 2011) revealed significant differences in the metabolism of certain compounds such as α-D-glucose, D-fucose, inosine, L-Malic Acid, α-keto-butyric acid, and propionic acid (Table 1).…”
Section: Cellular Biochemical and Phenotypic Characterization Of Yell...mentioning
confidence: 99%
See 2 more Smart Citations